Impact Evaluation of the DFID Programme to Accelerate Improved Nutrition of the Extreme Poor in Bangladesh - Hoddinott, John F.; Roy, Shalini; Karachiwalla, Naureen; Naher, Firdousi; Nisbett, Nick; Tranchant, Jean Pierre (International Food Policy Research Institute, 2013)
Undernutrition is widespread in Bangladesh. In 2011, according to the Bangladesh Demographic and Health Survey, 41.3 per cent of children under age five were stunted, 36.4 per cent were underweight, 15.6 per cent were wasted, and more than 50 per cent were anaemic. Prevalences were even higher among extremely poor households. Meanwhile, evidence from South Asia shows that high rates of economic growth and reduction in poverty have not led to similarly large reductions in undernutrition (see 1, 2, 3). These findings have suggested that improvements in income alone may not be sufficient to improve nutritional status. Extensive research has also shown that the critical window for nutritional interventions is during the "first thousand days" of life (see 4, 5), from the time when a child is in utero until about two years of age. Based on this accumulated evidence, growing attention has come to introducing nutrition interventions that target children's "first thousand days" alongside household poverty reduction programmes. In particular, there has been growing emphasis on nutrition interventions that aim to improve infant and young child feeding practices—through increasing nutritional knowledge of women who are pregnant, lactating, or likely to be pregnant in the future—as well as to improve the nutritional status of these women themselves.